2011
DOI: 10.1097/mpa.0b013e318212c02c
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Physiologic Ability and Surgical Stress Score Does Not Predict Immediate Outcome After Pancreatic Surgery

Abstract: The Estimation of Physiologic Ability and Surgical Stress scoring system is an ineffective predictor of complications after pancreatic resection. Further refinements to the score calculation are warranted to provide accurate prediction of immediate surgical outcome after pancreatic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Accurate identification of patients at high risk of perioperative morbidity can guide patient-physician discussions prior to surgery, as well as identify appropriate patients for “pre-habiliation.” 11 Several studies have demonstrated that active alcoholism, coagulopathy, jaundice, acute renal failure, heart disease, and obesity are associated with increased postoperative morbidity and mortality after pancreatic resection. 1214 More recently, there has been interest in identifying more general parameters of “health” to risk stratify patients.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate identification of patients at high risk of perioperative morbidity can guide patient-physician discussions prior to surgery, as well as identify appropriate patients for “pre-habiliation.” 11 Several studies have demonstrated that active alcoholism, coagulopathy, jaundice, acute renal failure, heart disease, and obesity are associated with increased postoperative morbidity and mortality after pancreatic resection. 1214 More recently, there has been interest in identifying more general parameters of “health” to risk stratify patients.…”
Section: Introductionmentioning
confidence: 99%
“…While several scoring systems have been proposed, their prognostic accuracy in quantifying the risk associated with patient-level physiological/performance status has been questioned. 15-17 Frailty has been proposed as a more global metric of patient physiological reserve and overall health status. 32 Frailty can be assessed utilizing patient questionnaires or varied clinical measurements of weakness or physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have suggested the Estimation of Physiologic Ability and Surgical Stress Scoring (E-PASS) system as a more comprehensive physiologic estimation; however, results have been mixed. 15-17 Frailty, a measure believed to estimate a patient’s physiologic reserves, has recently been proposed as a more robust predictor of outcomes following surgery. 18,19 Initial assessments of frailty have been criticized for relying on scales dependent on subjective evaluations of weakness, exhaustion, and physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Deyle et al. analyzed 304 patients undergoing pancreatic resection and revealed no significant differences in E‐PASS scores between patients with and without postoperative complications. They concluded that E‐PASS is an ineffective predictor of complications after pancreatic resections.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, Deyle et al. reported that E‐PASS was an ineffective predictor of complications following pancreatic resection. Similar contradictive results have been reported on the accuracy of POSSUM models in pancreatic resections .…”
Section: Introductionmentioning
confidence: 92%